PO129 Neda analysis by epoch in the opera studies of ocrelizumab. (1st December 2017) - Giovannoni, Gavin; Arnold, Douglas L; Bar-Or, Amit; Havrdová, Eva; Kappos, Ludwig; Lublin, Fred; Traboulsee, Anthony; Belachew, Shibeshih; Han, Jian; Hauser, Stephen L
Abstract : Background: No Evidence of Disease Activity (NEDA) measures the absence of detectable clinical and magnetic resonance imaging (MRI) disease activity in relapsing multiple sclerosis. NEDA analyses using re-baselining may better reflect the effects of disease-modifying treatments. Objective: To assess the effect of ocrelizumab on NEDA by epoch in the pooled OPERA I/II (NCT01247324 /NCT01412333) studies. Methods: Patients received ocrelizumab 600 mg every 24 weeks or subcutaneous interferon beta-1a (IFNβ−1a) 44 µg three-times weekly for 96 weeks. Brain MRI was undertaken at baseline and Weeks 24, 48, and 96. NEDA (i.e., the absence of protocol-defined relapses, 12 week confirmed disability progression, new/enlarging T2 lesions and T1 gadolinium-enhancing lesions) was assessed from baseline-Week 96, baseline-Week 48, Week 48 Week 96, baseline-Week 24 and Week 24 Week 96. Results: Over 96 weeks, ocrelizumab was associated with a 75% increase in the proportion of patients with NEDA versus IFNβ−1a (p<0.0001). Compared with IFNβ−1a, ocrelizumab increased the proportion of patients with NEDA from baseline-Week 48 (56%), Week 48 Week 96 (43%), baseline-Week 24 (33%) and Week 24 Week 96 (72%; all epochs p<0.0001). Conclusions: A higher proportion of patients reached NEDA at first MRI (Week 24) with ocrelizumab versus IFNβ−1a; after re-baselining from Week 24–96, the proportion reaching NEDA increased further.